Golden Eagle in Karatau and Chu-Ili Mountains (Kazakhstan) and Assessment of Risks to its Populations from Developing Wind Energy - Igor V. Karyakin; Kirill I. Knizhov; Elvira G. Nikolenko; Elena P. Shnayder; Genriyetta I. Pulikova; Alyona G. Kaptyonkina (Пернатые хищники и их охрана)
The Golden Eagle (Aquila chrysaetos) is the largest eagle in Kazakhstan, breeding in almost all mountainous and forested areas of the country. In Karatau and the Chu-Ili Mountains, there are large breeding groups of this species, which have been threatened by the development of a network of wind power plants (WPPs) since 2021 since both of these breeding groups are concentrated in powerful wind corridors that are promising for wind energy generation. During the work, we modelled the distribution of the Golden Eagle in Karatau and the Chu-Ili Mountains using the Random Forest image classification method, calculated its numbers in this area and assessed the threats to its breeding groups from both existing and prospective WPPs. The area of breeding biotopes for the Golden Eagle is 18209.9 km2, and the area of habitats is 67602.43 km2. The Golden Eagle population in Karatau as of 2024 is estimated at 434–645, on average 466 breeding pairs (80 breeding territories are known), and 1126–1674, an average of 1209 ind., taking into account fledglings of the current year and immature eagles, in the Chu-Ili Mountains – at 163–292, on average 222 breeding pairs (40 breeding territories is known), and 422–757, on average 575 ind. The number of Golden Eagles migrating through Karatau is estimated at 7276–11423, with an average of 8386 ind. In the zone of influence of the Zhanatas and Shokpar windfarms, which has a radius of 4.5 km, three pairs of breeding Golden Eagles disappeared over 3 years. Some of the birds from the disbanded pairs died due to collisions with the blades of wind turbines, which is confirmed by the remains of 2 Golden Eagles under the turbines. Based on calculations in the CRM “Band”, a risk map with a cell step of 5 km was created, representing an assessment of the probable mortality of eagles during the construction of wind farms in these cells. The results of this study apply to the conservation planning efforts of the Golden Eagle, analysing the risks of developing not only wind energy but also other land uses, including mining and even recreation, and implementing compensatory measures for human intervention in the Goolden Eagle's habitat.